S-Carvone Suppresses Cellulase-Induced Capsidiol Production in Nicotiana tabacum by Interfering with Protein Isoprenylation . Issue 2 (23rd December 2013) - Huchelmann, Alexandre; Gastaldo, Clément; Veinante, Mickaël; Zeng, Ying; Heintz, Dimitri; Tritsch, Denis; Schaller, Hubert; Rohmer, Michel; Bach, Thomas J.; Hemmerlin, Andréa
Abstract : In cellulase-elicited Nicotiana tabacum leaves, a monoterpene controls the biosynthesis of capsidiol, a sesquiterpene phytoalexin, by inhibiting the modification of proteins with a geranylgeranyl group . Abstract: S -Carvone has been described as a negative regulator of mevalonic acid (MVA ) production by interfering with 3-hydroxy-3-methyl glutaryl coenzyme A reductase (HMGR) activity, a key player in isoprenoid biosynthesis. The impact of this monoterpene on the production of capsidiol in Nicotiana tabacum, an assumed MVA -derived sesquiterpenoid phytoalexin produced in response to elicitation by cellulase, was investigated. As expected, capsidiol production, as well as early stages of elicitation such as hydrogen peroxide production or stimulation of 5- epi -aristolochene synthase activity, were repressed. Despite the lack of capsidiol synthesis, apparent HMGR activity was boosted. Feeding experiments using (1- 13 C)Glc followed by analysis of labeling patterns by 13 C-NMR, confirmed an MVA -dependent biosynthesis; however, treatments with fosmidomycin, an inhibitor of the MVA -independent 2-C-methyl-d -erythritol 4-phosphate (MEP ) isoprenoid pathway, unexpectedly down-regulated the biosynthesis of this sesquiterpene as well. We postulated that S -carvone does not directly inhibit the production of MVA by inactivating HMGR, but possibly targets an MEP -derived isoprenoid involved in the early steps of the elicitation process. A new model is proposed in which the monoterpene blocks an MEP pathway–dependent protein geranylgeranylation necessary for the signaling cascade. The production of capsidiol was inhibited when plants were treated with some inhibitors of protein prenylation or by further monoterpenes. Moreover, S -carvone hindered isoprenylation of a prenylable GFP indicator protein expressed in N. tabacum cell lines, which can be chemically complemented with geranylgeraniol. The model was further validated using N. tabacum cell extracts or recombinant N. tabacum protein prenyltransferases expressed in Escherichia coli . Our study endorsed a reevaluation of the effect of S -carvone on plant isoprenoid metabolism.